Extending employment beyond the pensionable age: a cohort study of the influence of chronic diseases, health risk factors, and working conditions. - Marianna Virtanen; Tuula Oksanen; G David Batty; Leena Ala-Mursula; Paula Salo; Marko Elovainio; Jaana Pentti; Katinka Lybäck; Jussi Vahtera; Mika Kivimäki (PLoS ONE)
Background In response to the economic consequences of ageing of the population, governments are seeking ways with which people might work into older age. We examined the association of working conditions and health with extended employment (defined as >6 months beyond the pensionable age) in a cohort of older, non-disabled employees who have reached old-age retirement. Methods A total of 4,677 Finnish employees who reached their old-age pensionable date between 2005 and 2011 (mean age 59.8 years in 2005, 73% women) had their survey responses before pensionable age linked to national health and pension registers, resulting in a prospective cohort study. Results In all, 832 participants (17.8%) extended their employment by more than 6 months beyond the pensionable date. After multivariable adjustment, the following factors were associated with extended employment: absence of diagnosed mental disorder (OR 1.25, 95% confidence interval = 1.01-1.54) and psychological distress (OR 1.68; 1.35-2.08) and of the work characteristics, high work time control (OR 2.31; 1.88-2.84). The projected probability of extended employment was 21.3% (19.5-23.1) among those free of psychiatric morbidity and with high work time control, while the corresponding probability was only 9.2% (7.4-11.4) among those with both psychiatric morbidity and poor work time control. The contribution of chronic somatic diseases was modest. Conclusions In the present study, good mental health in combination with the opportunity to control work time seem to be key factors in extended employment into older age. In addition, high work time control might promote work life participation irrespective of employees' somatic disease status.